A View on Genesis Myth and the Seventeenth Century English Literature: Exploring the Influence of Genesis Myth in 17th Century English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This section of the present paper covers a critical survey of English literature of the 17th century that relates to the genesis myth, the Christianity, the Bible, the Church of England and Puritanism. The 17th century English literature may best be described as the age from Donne to Dryden, covering such great writers as Shakespeare, Ben Jonson, Pope, the Metaphysical Poets, Banyan and finally Milton.